Simulation and the simulation language SLAM II as a systems analysis tool - P. S. Kruger; P. Lindeque; K. Adendorff (South African Journal of Business Management, 1989)
This paper provides a general introduction to the simulation technique and the simulation language SLAM II. The use of simulation modelling and in particular SLAM II is demonstrated by way of an illustrative example consisting of the building and manipulation of a simulation model of a materials handling subsystem of a beer brewing and packaging plant. The purpose of the model is to investigate the influence of the number of loading and unloading docks on various measures of system performance.
Keywords: 650